2015
DOI: 10.1177/0734371x15578534
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Job Satisfaction Correlates in the Public Administration Literature

Abstract: What can we learn by applying a meta-analysis to the public administration literature on job satisfaction? More generally, how can public management scholars use this method to capitalize on the decades of research on other topics within our field? This study reports the findings of the first quantitative review of the public administration literature on job satisfaction. We retrieved quantitative data from primary studies published in 42 public administration journals since 1969 and performed a meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
2
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 122 publications
(103 reference statements)
5
155
2
18
Order By: Relevance
“…Lastly, we fully acknowledge that our research synthesis is not immune to the same limitations that impinge on any effort to systematically review available evidence on a topic of interest (e.g., Bellé and Cantarelli ; Cantarelli, Belardinelli, and Bellé ; Gerrish ; Ritz, Brewer, and Neumann ). Those limitations should be taken into full account when considering the findings and the implications of our work.…”
Section: Implications For Public Administration Management and Policymentioning
confidence: 99%
“…Lastly, we fully acknowledge that our research synthesis is not immune to the same limitations that impinge on any effort to systematically review available evidence on a topic of interest (e.g., Bellé and Cantarelli ; Cantarelli, Belardinelli, and Bellé ; Gerrish ; Ritz, Brewer, and Neumann ). Those limitations should be taken into full account when considering the findings and the implications of our work.…”
Section: Implications For Public Administration Management and Policymentioning
confidence: 99%
“…According to Cantarelli, Belardinelli, and Belle (2015), the concept of job satisfaction has drawn considerably more attention than any other concept in the field of public administration. While job satisfaction alone may represent an important area of study, an important case for examining job satisfaction is that its byproducts (e.g., turnover and organizational commitment) represent some of the raw materials required for organizational performance.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Future research should also consider the inclusion of additional LGBT job satisfaction correlates highlighted by Cantarelli et al (2015) to further understand the factors that impact the job satisfaction of marginalized groups. For example, Ko, Hur, and Smith-Walter (2013) found that worklife benefits impact employee job satisfaction.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…A question which remains prominent is what the relationship is between pride and other positive psychological concepts such as organizational commitment (Meyer & Allen, 1991), Public Service Motivation (Leisink & Steijn, 2009;Pandey & Stazyk, 2008), and job satisfaction (Cantarelli, Belardinelli, & Belle, 2016). Studies focusing on work engagement and inherently pride showed that commitment with the organization, job satisfaction, and public service motivation are job attitudes which work in tandem to produce organizational outcomes (Albrecht et al, 2015;Perry & Vandenabeele, 2015).…”
Section: Theorymentioning
confidence: 99%
“…First, occupational expertise refers to the personal qualities and capabilities that are needed to reach given attainments (Van der Heijden, 2000). Occupational expertise might be especially important in the increasing demanding work environment of public servants nowadays (Cantarelli et al, 2016). It might be expected that public servants remain proud within an era of doing more with less means if they have enough occupation specific expertise to keep doing their job.…”
Section: Factors From the Jd-r Modelmentioning
confidence: 99%